ID 213 – Comparative study between intra-epidermal electric stimulation and laser stimulation for C-fiber activation. Do we stimulate the same C-fibers?. Issue 3 (March 2016) - Hagiwara, K.; Perchet, C.; Bastuji, H.; Garcia-Larrea, L.
Abstract : Objective: Intra-epidermal stimulation (IES) has firstly been introduced for A™-fiber activation, but it has recently been utilized by Japanese researchers for C-fiber activation. We aimed to carefully examine the feasibility of IES in comparison to the laser stimulation. Methods: IES was delivered as train stimuli (50 Hz; duration 200 ms; inter-trial interval 10 ± 2 s; approximately 15 trains) consisted of square-wave pulse of 0.6 ms duration (triangular pulse is theoretically ideal, but we prioritized the feasibility). Intensity was adjusted to above pain threshold (could be 2 mA) for practical use. Event-related potentials were evaluated in comparison to laser stimuli in both A-delta and C-warmth mode. Results: Despite the square-wave pulse and relatively unstable sensation, IES elicited a vertex-positive component at around 1000 ms in parallel with motor response, which was therefore consistent with a selective activation of C-fibers, at least in glabrous skin. Latencies of the IES-elicited and laser-driven C-responses significantly differed, suggesting that the two stimulation methods activate a different pool of C-fibers. Should this be confirmed, it could provide interesting application to differentiate sub-system alteration in clinical settings. Conclusions/Key message: The pool of C-fibers activated by IES appears different from that activated by warm-laser stimuli.